New species of Nymphites Haase (Neuroptera: Nymphidae) from the Middle Jurassic of China, with a redescription of the type species of the genus - Shi, Chaofan; Makarkin, Vladimir N.; Yang, Qiang; Archibald, S. Bruce; Ren, Dong (Zootaxa, 2013)
Nymphites priscus (Weyenbergh, 1869) from the Late Jurassic of Solnhofen (Germany), type species of the genus Nymphites Haase, 1890, is redescribed. The genus is assigned to the Nymphidae. The taxon Nymphitidae is not valid; it is an artificial aggregation of fossil genera. Two species new to science, one named, of Nymphites from the Middle Jurassic locality of Daohugou (Inner Mongolia, China) are described.